From Routine Work to Creative Initiative: How Do School and University Influence the Formation of Personal Qualities and Skills? - E. A. Kogan; E. I. Pronina (Высшее образование в России)
School and university, as two stages of continuous education, have a significant impact on forming a young person’s personality. When studying at school, young people cannot always appreciate the usefulness of their knowledge, skills, qualities, and applicability in further studies and life. The article presents the results of the sociological survey on the influence of school and higher education institutions on the development of students’ personal qualities and skills.The empirical base was the results of a study conducted among 1–3-year students of four Moscow universities: Moscow Aviation Institute (NRU), Moscow State Pedagogical University, Moscow Automobile and Road Construction Institute, and the State Academic University for the Humanities. Questionnaires and mini-interviews were used as research methods. The purpose of the study was to identify the specifics of the influence of school and university on the formation of students’ personal qualities and skills in the Moscow region.The survey showed that school had the most significant influence on forming the ability to communicate, perform routine work, and subject to the rules, and such qualities as discipline, stress resistance, adaptability, tolerance. While at university, students learn to take the initiative, set goals and realize them, defend their opinion and solve non-standard tasks, be independent and flexible.The survey participants would like the school to be more focused on developing students’ creative abilities and their own opinions; they lack practice and interaction in the classroom and an individual approach. Nevertheless, many qualities and skills developed at school helped them study at university.